Role of glucocorticoids in development and growth of the cardiovascular system in the zebrafish - Wilson, Kathryn Sarah (The University of Edinburgh, 2014)
INTRODUCTION: Glucocorticoids (GCs) are synthesised endogenously in mammals by the hypothalamic pituitary adrenal (HPA) axis in response to stress. These hormones can elicit a number of physiological roles by binding to and activating specific receptors (glucocorticoid or mineralocorticoid receptors- GR or MR). GCs are important in tissue development and maturation and commonly used therapeutically. Mammalian animal studies have suggested that over-exposure to GCs, whether pharmacologically or through induction of maternal stress, is associated with increased cardiovascular disease risk in adult life. The underlying mechanisms underpinning this early life programming are poorly understood, however GC exposure during development may have direct and indirect effects on the structure and function of developing tissues and organs which may predispose to disease in later life. Current mammalian models of programming do not lend themselves well to studying organ development during embryogenesis. The zebrafish provides an ideal model to study this phenomenon due to the transparent nature of developing larvae and the availability of transgenic lines expressing fluorescent markers. METHODS: GC pathways were comprehensively characterised during zebrafish embryo development using qRT-PCR and steroid ELISAs. The physiological roles of GCs were assessed during early zebrafish development (first 120 hours post fertilisation (hpf)) assessing stress response, swim activity and global development following various genetic and pharmacological manipulations of the GC system. The impact that GC manipulation had on the cardiovascular system was also investigated. Embryos which had been exposed to GC manipulation during early development were then allowed to develop to adulthood in order to assess the long term impact. The same parameters were investigated in the adult as in the embryo. RESULTS: The key components of the GC system are present and functional in the developing embryo with de novo cortisol biosynthesis evident from 48hpf. A functioning hypothalamic pituitary inter-renal (HPI) axis is demonstrable from 72hpf. Manipulation of specific components of the GC pathway during early embryonic development influences growth-rate, head-trunk angle, chorion hatch-rate and swim behaviour. Manipulation of GCs during embryogenesis resulted in altered body weight, length and girth in adulthood, with altered stress response and swim behaviour also detected. Embryonic heart development was also affected with a reduction in ventricle cardiomyocyte number, cardiac gene abundance (vhmc) and cardiac function during embryogenesis resulting in structural abnormalities such as fewer trabeculae and increased intra-ventricular space. Embryonic GC manipulation also alters the formation and patterning of intersegmental blood vessels by 120hpf. In adulthood this manifests as a reduced angiogenic capacity. CONCLUSION: The zebrafish embryo represents a valid and physiologically relevant model for GC research. Manipulation of GCs during early development results in altered growth, gene abundance and cardiovascular structure. These findings have significant implications for on-going research addressing GC mediated programming and suggest that the zebrafish is a highly suitable model for GC research
Keywords: zebrafish; glucocorticoids; early life programming